RT-qPCR assay for detection of mink astrovirus in outbreaks of diarrhea on Danish mink farms. - Sofie Barsøe; Karin Ullman; Mikael Leijon; Kjell Olof Hedlund; Jonas Klingström; Louise Iuel Krarup; Lars Andresen; Michelle Lauge Quaade; Anne Sofie Hammer (PLoS ONE)
Diarrhea in mink kits is a major cause of disease and mortality in the mink production. The etiology remains unknown in most outbreaks due to a lack of diagnostic assays. In the current study we present an RT-qPCR method to detect mink astrovirus in fecal samples from mink kits with diarrhea. All sampled animals were classified based on age and patoanatomical evaluation as having pre-weaning diarrhea, diarrhea in the growth period or as having no macroscopic signs of diarrhea. Fecal samples were analyzed for MiAstV with RT-qPCR, next generation sequencing and electron microscopy in parallel. Mink astrovirus was detected with RT-qPCR in 92 out of 203 samples. This detection was confirmed by next generation sequencing in a high proportion of samples (22/27), and by visualization of astrovirus particles with EM in some of the samples. Mink astrovirus was highly prevalent (68%) among kits in the outbreaks of pre-weaning diarrhea, in particular outbreaks from May, while less prevalent in outbreaks in June. Mink astrovirus was detected in outbreaks of diarrhea in the growth period, though in a much lesser extent than in the pre-weaning period. The role of mink astrovirus in the diarrhea disease complex of mink remain to be investigated, and for that purpose this sensitive and robust RT-qPCR can be a valuable tool in the future.